2009
DOI: 10.1007/s00467-009-1196-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of postnatal dietary sodium in prenatally programmed hypertension

Abstract: In this study we examined the short- and long-term impact of early life dietary sodium (Na) on prenatally programmed hypertension. Hypertension was induced in rat offspring by a maternal low protein (LP) diet. Control and LP offspring were randomized to a high (HS), standard (SS), or low (LS) Na diet after weaning. On the SS diet, the LP pups developed hypertension by 6 weeks of age. The development of hypertension was prevented by the LS diet and exacerbated by the HS diet. Kidney nitrotyrosine content, a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…When LP pups were weaned onto a low-(0.03%), standard-(0.3%), or high-(3%) salt diet for 3 weeks, there was a positive correlation between salt intake and blood pressure in LP rats but not controls. Longitudinal blood pressure profiling showed that brief exposure to a low-salt diet had a long-lasting antihypertensive effect, whereas those briefly fed a high-salt diet continued to have increased blood pressure up to 51 weeks of age [30].…”
Section: Discussionmentioning
confidence: 99%
“…When LP pups were weaned onto a low-(0.03%), standard-(0.3%), or high-(3%) salt diet for 3 weeks, there was a positive correlation between salt intake and blood pressure in LP rats but not controls. Longitudinal blood pressure profiling showed that brief exposure to a low-salt diet had a long-lasting antihypertensive effect, whereas those briefly fed a high-salt diet continued to have increased blood pressure up to 51 weeks of age [30].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic and vascular disorders, themselves "perinatally programmed", may additionally affect renal function and renal structure and lead to hypertension and early chronic kidney disease (see text). ESRD end-stage renal disease, IUGR intrauterine growth restriction, GFR glomerular filtration rate, GC glucocorticoids, GS glomerular sclerosis, HTN hypertension, P GC glomerular capillary pressure, SNGFR single nephron glomerular filtration rate glomerular hyperfiltration and induce systemic hypertension and glomerular injuries in adult animals with a reduced nephron number [83,93,94,111,157]. Such a sequence has been shown to result from an up-regulation of the RAS [110,158].…”
Section: Experimental Studiesmentioning
confidence: 96%
“…This provides evidence of abnormal programming of the RAS and glomerular function in offspring of pregnancies in which there is impaired maternal renal function [105]. Aside from reduced nephron endowment, hypertension can be due to an alteration in the tubular handling of sodium with increased sodium reabsorption, over-activity of the sympathetic nerve, and oxidative stress [34,63,[106][107][108][109][110][111]. Increased expression of the renal tubular Na+:K+:2Cl-co-transporter (NKCC2) and loss of the Na+:K + ATPase alpha1 subunit from the inner medulla have been demonstrated in MLP rat offspring, suggesting that altered renal sodium handling is also programmed prenatally [112].…”
Section: Altered Nephrogenesis and Increased Arterial Blood Pressure mentioning
confidence: 97%
See 1 more Smart Citation
“…Rodents, in which nephrogenesis is completed during the first 2 weeks after birth, can be programmed during this period to develop hypertension in adult life by maneuvers such as protein restriction 1 and dietary salt overload. 2 The mechanisms responsible for blood pressure heightening in this setting are presently obscure, and may involve subtle changes in renal handling of sodium. 3 Treatment with suppressors of the renin-angiotensin system (RAS) during rat lactation (first 3 weeks after birth) has also been shown to promote hypertension later in life.…”
Section: Introductionmentioning
confidence: 99%